The Effect of Islamic Corporate Governance Disclosure in Financial Performance Me-diation on Islamic Social Reporting - Ade Onny Siagian; Asep Muhammas Lutfi; Aris Ariyanto; Hadion Wijoyo (Jurnal Ilmu Manajemen & Ekonomika, 2021)
The social role of Islamic banks shows inconsistencies both at home and abroad; this is the basis for con-ducting this research to re-explain the Islamic Corporate Governance (ICG) and Islamic Social Reporting (ISR) relationship, models. This study aims to examine the indirect effect of ICG disclosure on ISR disclo-sure with financial performance as a mediating variable in Islamic Banking in Indonesia. This study uses secondary data with annual report data sources and financial statements on Islamic banking in Indonesia. They are testing this study using stepwise regression analysis with data for the annual reporting period of 2016 through 2019. The result that financial performance mediates the effect of disclosure of ICG on ISR; this shows that proper management of Islamic banks will produce high financial performance so that they can carry out their social roles well too. The contribution of this study is to develop a new model of the part of financial performance mediating the effect of ICG disclosure on ISR so that it is beneficial for the development of science.